Case report: A balance of survival and quality of life in long-term survival case of lung adenocarcinoma with synchronous bone metastasis - Xu, Yao; Wu, Haixiao; Wang, Cong; Ma, Yulin; Zhang, Chao (Frontiers in Oncology, 2022)
Bone metastasis is one of the comorbidities of advanced lung cancer, eventually leading to an impaired quality of life. We present a case of a lung adenocarcinoma patient with synchronous bone metastasis. The patient possessed a superior survival time of more than five years under multidisciplinary treatment. Considering the balance of life expectancy and limb function, the metastatic site on the right humerus was successively surgically managed. Based on the present case, we emphasized the importance of treatment choice between anti-tumor and bone management in the long-term survival of cancer patients with synchronous bone metastasis.